Управління інтелектуальним капіталом підприємства - Якименко-Терещенко, Наталія Василівна; Чикота, К. В. (Хмельницький національний університет, 2018)
Досліджено підходи до визначення поняття «інтелектуальний капітал». Встановлено взаємозалежність та взаємозв’язок складових інтелектуального капіталу, що ефективно позначається на спроможності підприємства реалізовувати стратегію розвитку в умовах конкуренції на ринку. Визначено характерні риси інтелектуального капіталу та функції, які він виконує. Сформовано авторську точку зору на доцільність формування системи управління інтелектуальним капіталом як цілісну сукупність взаємопов'язаних і взаємозалежних спільно функціонуючих елементів з метою формування інтелектуального капіталу підприємства, його захисту, накопичення, поширювання та ефективного використання. Визначено, що інвестування в інтелектуальний капітал підприємства є одним з найбільш дієвих інструментів управління ним, засобом забезпечення ефективного функціонування та розвитку підприємства. Визначено особливості інвестицій в інтелектуальний капітал та зазначено про необхідність забезпечення їх збалансованості між елементами капіталу.

The approaches to the definition of «intellectual capital» are investigated. The interdependence and interconnection of the components of intellectual capital are established, which effectively affect the company’s ability to implement a development strategy in the conditions of competition in the market. Characteristic features of intellectual capital are determined, including intangible nature; affiliation at the same time to the stock and product; increase in consumption; storage and accumulation in nontraditional forms; acquiring the role of the main component of determining the degree of success and competitiveness of the enterprise. The main functions of intellectual capital are defined such as accumulation, production, reproduction, stimulation, and ensuring labour productivity. The author’s point of view on the expediency of forming an intellectual capital management system, which is an integral set of interrelated jointly functioning elements, is formed in order to form of the intellectual capital of the enterprise, it’s protection, accumulation, distribution and effective use. The subsystems of the intellectual capital management system are subsystems for the formation of intellectual capital; storage and protection; distribution and use. One of the main tasks of the intellectual capital management system is to create a mechanism for the rapid and qualitative transformation of the human (not belonging to the enterprise) into structural capital - one that is already the property of the enterprise. It is determined that investing in the intellectual capital of an enterprise is one of the most effective tools for managing it, as a means of ensuring the effective functioning and development of the enterprise. The features of investments in intellectual capital are determined, among which the proportional dependence of the degree of return on investment from the duration of the working period of the investment object; the propensity of the investment object to physical and moral depreciation; the existence of a point of maximum extreme profitability of investment in human capital, due to the upper limit of activity of labour activity; the dependence of nature, scale, types and ways of investing in human capital on historical, national, cultural characteristics, traditions of the population; the greatest efficiency for an individual, a company, a society in comparison with other kinds of investments; theoretically unlimited, but practically much longer investment period, etc. It is noted about the need to balance investment between elements of intellectual capital.
Intellectual capital management of the enterprise
Keywords: інтелектуальний капітал; управління; інвестиції; intellectual capital; management; investment